Pengaruh Model Pembelajaran Assurance, Relevance, Interest, Assessment And Satisfaction (ARIAS) Terhadap Hasil Belajar TIK (Case study of class X SMK Negeri 9 Padang) - Popi Radyuli; Lisa Aprila Aska (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2019)
AbstractThis study aims to determine the effect of assurance, relevance, interest, assessment and satisfaction (ARIAS) learning models on ICT learning outcomes in class X SMA Negeri 4 Padang even semester of the 2018/2019 academic year. The research method used was a quasi-experimental, sampling technique using purposive sampling. The sample in this study were students of class X MIPA 5 as an experimental class and class X MIPA 1 as a control class with the number of students in each class 32. The experimental class was treated with the application of assurance, relevance, interest, assessment and satisfaction (ARIAS) learning models and control class given conventional learning treatment. The research instrument used was a multiple choice test.The results of the study, obtained an average value of the experimental class was 83.37 and the average value of the control class was 78.75. From the test results at the significance level α 0.05 (at 5% level), the value of tcount = 2.980 and ttable = 1.669 so that it was obtained tcount> ttable (2.980> 1.669). Thus H0 is rejected and H1 is accepted, which means that the application of the Assurance, relevance, interest, assessment and satisfaction (ARIAS) learning model has a positive effect on the learning outcomes of class X ICT in SMA Negeri 4 Padang even semester of the 2018/2019 school year.